Phospholipase A2 inhibitors for the treatment of inflammatory diseases: A patent review (2010-present) - Magrioti, V.; Kokotos, G. (Expert Opinion on Therapeutic Patents, 2013)
Introduction: Phospholipases A2 have been implicated in various pathological conditions, such as rheumatoid arthritis, cardiovascular diseases, neurological disorders and cancer. The scientific community focuses on the search of potent and selective PLA2 inhibitors of each PLA2 class in order to identify novel medicinal agents. At present, only one lipoprotein-associated PLA2 (LpPLA2) inhibitor has reached Phase III clinical trials for the treatment of atherosclerosis. Areas covered: This review article focuses on the role of the most important PLA2s in inflammatory diseases and other severe pathological conditions presented in patent literature from June 2009 to September 2012. Expert opinion: Even though the role of each PLA2 in different diseases or pathological conditions is not yet definitively identified, the progress in the quest for potent and selective PLA2 inhibitors is exciting and the use of such inhibitors as medicinal agent looks now more promising than ever.